2011
DOI: 10.25011/cim.v34i6.15893
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological effects of fibrin glue on penile fracture in a rat model

Abstract: Purpose: To evaluate both histopathological e ects and potential clinical application of brin glue on the penile cavernosal tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…[ 23 ] However, in other studies by Akgül et al and Taşdemir et al, it was observed that fibrosis decreased in the tissues of rats that underwent primary repair after PF. [ 6 , 7 ] Similarly, in our study, it was observed that fibrosis did not increase in rats that underwent primary repair. Intense fibrosis was observed in the PA and PRA groups at the end of the study, although this was not statistically significant between the two groups (p=0.077).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…[ 23 ] However, in other studies by Akgül et al and Taşdemir et al, it was observed that fibrosis decreased in the tissues of rats that underwent primary repair after PF. [ 6 , 7 ] Similarly, in our study, it was observed that fibrosis did not increase in rats that underwent primary repair. Intense fibrosis was observed in the PA and PRA groups at the end of the study, although this was not statistically significant between the two groups (p=0.077).…”
Section: Discussionsupporting
confidence: 78%
“…In our study, hyperemia and bleeding were observed in all groups, similar to the study by Akgül et al[ 23 ] In another study conducted by Akgül et al, when cyanoacrylic glue (CG) was applied to PF animals, a decrease in hyperemia was observed, attributed to the hemostatic property of CG. [ 6 ] Therefore, we observed hyperemia and bleeding in all rat tissues. However, in our study, hyperemia was significantly less common in the PRA group.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Increased inflammation was reported in PF of rats (Akgul et al, 2008;Tasdemir et al, 2011). The inflammatory response involves perivascular infiltration of lymphocytes, monocytes, and neutrophils at the site of injury (Somers et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Sections were scored in accordance with the modified method of Tasdemir et al (2011) based on histopathological findings as: absent (-), slight (+), moderate (++) and extensive (+++).…”
Section: Histopathological Analysismentioning
confidence: 99%